Metabolic Pathways Involved in Carbon Dioxide Enhanced Heat Tolerance in Bermudagrass - Yu, Jingjin; Li, Ran; Fan, Ningli; Yang, Zhimin; Huang, Bingru (Frontiers in Plant Science, 2017)
Global climate changes involve elevated temperature and CO2 concentration, imposing significant impact on plant growth of various plant species. Elevated temperature exacerbates heat damages, but elevated CO2 has positive effects on promoting plant growth and heat tolerance. The objective of this study was to identify metabolic pathways affected by elevated CO2 conferring the improvement of heat tolerance in a C4 perennial grass species, bermudagrass (Cynodon dactylon Pers.). Plants were planted under either ambient CO2 concentration (400 μmol⋅mol-1) or elevated CO2 concentration (800 μmol⋅mol-1) and subjected to ambient temperature (30/25°C, day/night) or heat stress (45/40°C, day/night). Elevated CO2 concentration suppressed heat-induced damages and improved heat tolerance in bermudagrass. The enhanced heat tolerance under elevated CO2 was attributed to some important metabolic pathways during which proteins and metabolites were up-regulated, including light reaction (ATP synthase subunit and photosystem I reaction center subunit) and carbon fixation [(glyceraldehyde-3-phosphate dehydrogenase, GAPDH), fructose-bisphosphate aldolase, phosphoglycerate kinase, sedoheptulose-1,7-bisphosphatase and sugars) of photosynthesis, glycolysis (GAPDH, glucose, fructose, and galactose) and TCA cycle (pyruvic acid, malic acid and malate dehydrogenase) of respiration, amino acid metabolism (aspartic acid, methionine, threonine, isoleucine, lysine, valine, alanine, and isoleucine) as well as the GABA shunt (GABA, glutamic acid, alanine, proline and 5-oxoproline). The up-regulation of those metabolic processes by elevated CO2 could at least partially contribute to the improvement of heat tolerance in perennial grass species.